PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI MADRASAH ALIYAH SERBA BAKTI TASIKMALAY - Nurhayati1, Nurhayati; CS, Nurhamzah; Wawan, Wawan (THORIQOTUNA: Jurnal Pendidikan Islam, 2020)
This study aims to determine the positive effect between the teacher's pedagogical competencies on the learning motivation of students in the Madrasah Aliyah Serba Bakti of the Suryalaya Islamic Boarding School. The method used in this study is a descriptive method through a quantitative approach with a population of 357 people, and a sample of 36 people using data collection techniques namely questionnaires, observation, and documentation. To test variables x and y are done by determining the mean value which is interpreted using the interpretation scale classification, as well as for the relationship between variables x and y used Spearman Rank correlation analysis techniques, and hypothesis testing using t-test. Based on the results of data processing, it is found that the influence of teacher pedagogical competence on student motivation in Madrasah Aliyah Serba Bakti of the Suryalaya Islamic Boarding School has a significant positive effect with a sufficient category, proven rs = 0.522 at intervals 0.41 to 0.60 and t_count (3.57) is greater instead of t_table (1,691). Teacher pedagogical competence determines student learning motivation by 27.25% while the remaining 72.75% is determined by other factors.